A cluster-randomised controlled trial of a brief training session to facilitate general practitioner referral to smoking cessation treatment. Issue 3 (3rd June 2008) - McRobbie, H; Hajek, P; Feder, G; Eldridge, S
Abstract : Objectives: General practitioners (GPs) are the main source of referrals to specialist smoking cessation services (SSCS), but the referral rates are low. We evaluated effects of a brief GP training session on the number of referrals received by their local SSCS. Methods: A cluster-randomised controlled trial was undertaken across three East London primary care trusts. A total of 91 GPs were randomly allocated to a training session or usual care. Participants in the intervention arm were offered a 40-min training session addressing the rationale and skills for referral of smokers for treatment. Participants in the usual care arm received referral guidance by post. The main outcome measure was the number of referrals recorded by the SSCS over 3 months after the intervention. Results: Over the 3-month baseline period the average number of referrals per GP was 1.0 and 0.6 in the intervention and usual care arms, respectively. During the post-intervention period the mean number of referrals was 6.4 and 1.8 per GP. When adjusting for baseline variables the incidence rate ratio for the referrals from the intervention arm compared to usual care was 4.9 (p<0.001; 95 CI 1.7 to 14.7). Conclusion: A brief training session can significantly increase GP referral to smoking cessation services. Trial registration: National Research Register, Department of Health, UK N0261148824 (available online at: http://www.nrr.nhs.uk/ViewDocument.asp?ID  N0261148824 )